The fractal dimension-based descriptor of the microvascular pattern on the histological section : [complications after revision total knee arthroplasties] - Šrámek, Jaromír; Pierzynová, Aneta; Kučera, Tomáš (Lékař a technika, 2019)
The microvascular pattern in the histological section, i.e. the point-pattern composed of capillaries perpendicular to the plane of section, contains information about the three-dimensional structure of the capillary network. Histological processing is followed by the shrinkage of tissue of uncertain magnitude. In order to obtain relevant information, the scale-independent analysis is necessary. We used an approach based on the Minkowski cover of measured set. The true fractal dimension of the point pattern is obviously of zero, but the artificial result of the algorithm can be related to the complexity of shape. We fitted the log-log plot by the modified rounded ramp function and the slope of the oblique part was used as the fractal based descriptor. We demonstrated on histological samples of the heart that this fractal-based parameter has the property of scale and rotation invariance.
Keywords: Fractals; lidé; rozpoznávání automatizované; Image Interpretation, Computer-Assisted; Pattern Recognition, Automated; interpretace obrazu počítačem; Humans; Histological Techniques; histologické techniky; fraktály